Cloud computing: vision, architecture and characteristics - Moghaddam, F. F. (Institute of Electrical and Electronics Engineers Inc., 2016)
Cloud computing is an unprecedented paradigm for hosting and delivering resources by providing on-demand services. The rapid growth of using cloud-based services in recent years is an impossible fact to be denied as it has increased the efficiency in accessing to shared pools of configurable computing resources. According to this rapid growth, it is anticipated that cloud computing will be the most important and challenging issue in IT industry. Therefore, the state-of-the-art of cloud computing has been surveyed in this paper that involves definition and essential concepts, architecture, models, deployment types, key technologies and characteristics of cloud computing.